ORM1 Mediates Ln-IgG-Induced Podocyte Damage and Autophagy via the AMPK/mTOR Signaling - Jie Chen; Libin Zou; Lu Liu; Chunfeng Wu; Mi Hu (Organogenesis)
Podocyte damage is a central feature of lupus nephritis (LN), making the identification of potential therapeutic targets to prevent podocyte injury and improve treatment outcomes essential. ORM1 has been suggested as a significant candidate gene in LN. In this study, mouse podocytes were induced using Immunoglobulin G (IgG) extracted from lupus patients. To investigate the role of ORM1, ORM1 knockdown was performed, and the effects on podocyte viability and apoptosis were assessed using the cell counting kit-8 (CCK-8) assay and flow cytometry. Additionally, autophagy markers LC3II/I and p62 were measured by western blotting and immunofluorescence, and the expression of the AMPK/mTOR signaling pathway was evaluated using western blotting. The results showed an upregulation of ORM1 in the LN model. Upon stimulation with IgG from LN patients, ORM1 knockdown reversed the reduction in podocyte viability, decreased the apoptosis rate, and reduced the elevated levels of autophagy, followed by an increase in AMPK phosphorylation and a decrease in mTOR phosphorylation. In conclusion, these results suggest that ORM1 modulates the expression of autophagy-related components in podocytes through the AMPK/mTOR signaling pathway, thereby influencing podocyte damage in the LN model in vitro.